Effects of Thermosonication, Sonication and Mild Heating on Organoleptic Attributes of Three Red Fruit Juices - Hooshyar, Leila; Jafarizadeh-Malmiri, Hoda; Berenjian, Aydin; Hesari, Javad; Azadmard-Damirchi, Sodeif; Şengül, Memnune (Current Nutrition & Food Science, 2020)
Background: Colour and turbidity (appearance), odour and flavour, taste, and texture are the main parameters affecting consumer’s perception of juice quality. Anthocyanins, as natural antioxidant and water-soluble pigment, exist in red fruit juices which are extremely unstable and more susceptible to degradation. These mainly include anthocyanins, pigments, proteins, and vitamins that are thermally sensitive. Objective: The present study focuses on the treatment of three different fruit juices namely red grape, pomegranate, and sour cherry using different preservative methods and evaluation of their organoleptic properties. Methods: Four preservative methods including pasteurization (90°C for 30 sec), mild heat treatment (60°C for 4, 8 and 12 min), sonication (25°C) and thermosonication (90°C) using amplitude levels of 24.4, 42.7 and 61 μm for 4, 8 and 12 min, have been used for the treatment of the three selected fruit juices. Results: Obtained results indicate that untreated grape juice had maximum L* value (29.83) and the pasteurized grape juice had a minimum L* value (25.77). Furthermore, while a* values of untreated grape, pomegranate, and sour cherry juices were 39.7, 42.03 and 38.13, respectively, these pasteurized juices had minimum a* values of 35.3, 38.47 and 36.97, respectively. In addition, results revealed that sonication and mild heating had minimum effects on colour and appearance, odour and flavour of all three studied juices. Furthermore, significant positive (p#130;0.05) effects of thermosonication were observed for the cloudiness parameter of the studied juices. Maximum acceptability scores were achieved by mild heat-treated grape juice at 60°C for 8 min (8.33), thermosonicated pomegranate juice at 60°C and amplitude of 24.4 μm for 4 min (7.33) and sonicated sour cherry juice at 25°C and amplitude of 24.4 μm for 4 min (9.33). Conclusion: Different preservative methods with optimum processing conditions were successfully utilized to minimize the changes in the sensorial and physicochemical properties of the treated juices.
Keywords: red fruit juices